Grassland renewal dominates multi-year nitrous oxide emissions in boreal legume grassland: Insights from eddy-covariance measurements - Li, Yuan; Thentu, Tulasi Lakshmi; Martikainen, Pertti J.; Virkajärvi, Perttu; Bhattarai, Hem Raj; Shurpali, Narasinha (Elsevier, 2026)
Nitrous oxide (N2O) emissions from agricultural soils represent the dominant source of this potent greenhouse gas, yet the interactions between management practices and environmental drivers governing these emissions remain poorly quantified, particularly across the entire grassland rotation cycle including renovation phases. We conducted three-year eddy covariance measurements of N2O fluxes from a legume-based grassland in eastern Finland, comparing mineral nitrogen (Nmin) and cattle-slurry digestate (Norg) fertilization strategies across the first (R1) and second grass production years (R2), and the renovation year (R3). Annual N2O emissions increased through the rotation and ranged from 1.9 to 3.4 kg N2O-N ha−1 under Nmin and 2.6–5.4 kg N2O-N ha−1 under Norg treatments. Emission factors ranged from 1.79 % to 7.56 % (Nmin) and 2.65–3.06 % (Norg). Grassland renewal increased emissions by 55 % (Nmin) and 80 % (Norg) relative to grass production years (R2). Environmental controls diverged between treatments: ecosystem respiration as the primary driver of N2O emissions under Nmin, while soil temperature dominated under Norg. N2O emissions during non-growing season contributed 22–35 % of annual budgets. Grassland renovation represents the critical emission hotspot within boreal grassland rotation cycles, overriding fertilizer type effects. Norg produced 37–59 % higher cumulative emissions. These findings highlight the critical importance of grassland management event and fertilizer type in N2O emission mitigation strategies and warrant eddy-covariance measurements for more accurate N2O emission inventories from boreal grasslands.
Keywords: boreal grassland; emission factors; eddy covariance; nitrous oxide; grassland renewal